The legacies of modernism : historicising postwar and contemporary fiction - James, David Ed (Cambridge University Press, 2012)
"An engagement with the continued importance of modernism is vital for building a nuanced account of the development of the novel after 1945. Bringing together internationally distinguished scholars of twentieth- and twenty-first-century literature, these essays reveal how the most innovative writers working today draw on the legacies of modernist literature. Dynamics of influence and adaptation are traced in dialogues between authors from across the twentieth century: Lawrence and A. S. Byatt, Woolf and J. M. Coetzee, Forster and Zadie Smith. The book sets out new critical and disciplinary foundations for rethinking the very terms we use to map the novel's progression and renewal, enhancing our understanding not only of what modernism was but also what it might still become. With its global reach, The Legacies of Modernism will appeal to scholars working not only in the new modernist studies, but also in postcolonial studies and comparative literature"--